Some Inequalities Concerning the Polar Derivative of a Polynomial-II (Analysis in Theory and Applications, 2013)
In this paper, we consider the class of polynomials $P(z)=a_{n}z^{n}+\sum_{ u=μ}^{n}a_{n- u}z^{n- u}$, $1≤ μ≤ n$, having all zeros in $|z|≤ k$, $k≤ 1$ and thereby present an alternative proof, independent of Laguerre's theorem, of an inequality concerning the polar derivative of a polynomial.
Keywords: Polar derivative of a polynomial.